GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1842 species occurrences available in GBIF matching the query: TaxonKey: Chrysodeixis Hübner, 1821. The dataset includes 1842 records from 62 constituent datasets: 46 records from International Barcode of Life project (iBOL). 10 records from Landesmuseum Kärnten. 76 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 3 records from Lund Museum of Zoology - Insect collections (MZLU). 3 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Artdata. 178 records from Museum Victoria provider for OZCAM. 2 records from Museum of Comparative Zoology, Harvard University. 173 records from iNaturalist Research-grade Observations. 9 records from Estonian University of Life Sciences. 22 records from Essig Museum of Entomology. 13 records from Collection entomologique Barthélémy. 2 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 7 records from naturgucker. 3 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 113 records from Taiwan Forestry Research Institute. 4 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 6 records from Akita Prefectural Museum, Insect Collection. 5 records from Insect (JNHM-IN). 3 records from Insect (JJHA-IN). 2 records from Insect (MNHM-IN). 19 records from Data on moths from automatically operating light traps in Denmark. 119 records from Tiroler Landesmuseum Ferdinandeum. 3 records from Norwegian Lepidoptera working group. 2 records from Naturhistorisches Museum Mainz, Zoological Collection. 14 records from Natural History Museum (London) Collection Specimens. 1 records from NMNH Extant Specimen and Observation Records. 3 records from Kashihara City Museum of Insect. 3 records from Insect Specimen Database of Fukui City Museum of Natural History. 2 records from Osaka Prefectural Minoh Park Insects Museum. 20 records from Lepidoptera Observations from New Zealand by Donald Hobern. 35 records from Biologiezentrum Linz. 2 records from Lepidopteran specimens of Iwate Prefectural Museum. 18 records from European Moth Nights. 2 records from Insect specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 18 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 88 records from Bugbase, Lepidopterological Society. 2 records from Biodiversitätsdatenbank des Landes Salzburg. 52 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 30 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 5 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 7 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from Insect Collection of Natural History Museum and Institute, Chiba. 7 records from Biological and palaeontological collection and observation data MNHNL. 93 records from Entomology Division, Yale Peabody Museum. 157 records from Insect (KNAM-IN). 2 records from Museum of Southwestern Biology, Division of Arthropods. 32 records from “Endemic Species Research Institute Moth Survey” Dataset. 30 records from Geographically tagged INSDC sequences. 1 records from Norwegian Species Observation Service. 8 records from TESRI-FB-EnjoyMoths. 23 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 145 records from Insect Collection of Taiwan Forestry Research Institute. 2 records from Queen Victoria Museum Art Gallery provider for OZCAM. 83 records from Natural History Museum Rotterdam (NL) - Insecta collection. 17 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 7 records from Australian Museum provider for OZCAM. 2 records from Entomology at ZMUC, Natural History Musem of Denmark. 2 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 46 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 55 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Insect (KDIR-IN). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences